Obesity management: lifestyle and bariatric surgery 2 - Wilding, John (Henry Stewart Talks, 2015)
Obesity outcomes that matter to patients, Options beyond lifestyle: pharmacotherapy and bariatric surgery, Effects of bariatric surgeries on obesity co-morbidities, Bariatric surgery: limitations, adverse effects and follow up